Government Debt Approach on Growth - Adhikari, Padam Kumar; Gajurel, Ram Prasad (Economic Review of Nepal, 2020)
This study aims to analyze the short-run and long-run relationship of nominal GDP (a dependent variable) with the four independent variables, such as domestic loans (dl), foreign loans (fl), export (exp), and gross fixed capital formation (gfcf). Both descriptive and inferential tools were used in this study: the five years of time series data from FY 2015 to FY 2020 under the descriptive design to examine the trends of these five study variables, and the 46 years of data from FY 1975 to FY 2020 and a multiple regression model under the inferential design to measure their relationship. Based on the objective and method, the study found the Nepali economy to be buckling under the weight of a growing and chronic public debt burden since the start of its budgetary process. Therefore, it behooves the government of Nepal to steer its economy towards positive growth in the future by mitigating the adverse effects of the debt burden.